Intermittent instability is widespread in plankton communities. (27th January 2023) - Rogers, Tanya L.; Munch, Stephan B.; Matsuzaki, Shin‐ichiro S.; Symons, Celia C.
Abstract: Chaotic dynamics appear to be prevalent in short‐lived organisms including plankton and may limit long‐term predictability. However, few studies have explored how dynamical stability varies through time, across space and at different taxonomic resolutions. Using plankton time series data from 17 lakes and 4 marine sites, we found seasonal patterns of local instability in many species, that short‐term predictability was related to local instability, and that local instability occurred most often in the spring, associated with periods of high growth. Taxonomic aggregates were more stable and more predictable than finer groupings. Across sites, higher latitude locations had higher Lyapunov exponents and greater seasonality in local instability, but only at coarser taxonomic resolution. Overall, these results suggest that prediction accuracy, sensitivity to change and management efficacy may be greater at certain times of year and that prediction will be more feasible for taxonomic aggregates. Abstract : Time‐varying local stability metrics were examined for plankton time series from 21 sites. We found that local stability metrics often fluctuated seasonally between stable and unstable values, suggesting that prediction accuracy, sensitivity to change and management efficacy may be greater at certain times of year than others. Taxonomic aggregates were more stable and more predictable than finer groupings and showed variation in stability with latitude.